Fair Water Pricing For Sustainable Management Of Available Water In India - Pooja Mehra, Saurabh Verma, Gurinderjit Kaur (International Journal of Advanced Science and Technology, 2020)
Adequate availability of freshwater will be the most challenging issue of the 21st century because of its scarcity. Water is regarded as a free good and a gift of nature, but it involves a massive cost for its collection, storage, groundwater pumping and delivery to potential users. Presently its cheap availability to farmers, domestic user and individuals resulting enormous loss of water and low water use efficiency. Appropriate water pricing and strong political will towards strict compliance of rules & regulation for recovery of at least cost of operations and maintenance of water delivery systems are needed for sustainable water management in India. Presently there is no provision to price irrigation water on a volumetric basis, and irrigation water charges are negligible. Irrigation water should be supplied on a volumetric basis, and water pricing should be on a national basis. Studies on the urban water supply of a few big cities indicate better pricing of domestic and industrial water supplies as compared to irrigation water. Groundwater extraction should also be charged adequately to check overexploitation. Virtual water of agricultural products and water footprint should also be considered for crop diversification and export/import of agricultural products.